Patients’ satisfaction with complete dentures: an update. - Marchini, Leonardo (Brazilian Dental Science, 2014)
Population aging is a worldwide phenomenon and, even though there is a downward trend in edentulism, the need for complete dentures is not likely to decrease in the near future. Furthermore, patients’ satisfaction with their dentures is fundamental to improving oral health-related quality of life among edentulous individuals. Considering this, a search was performed for literature since 2001 on the factors that may influence patient satisfaction with complete dentures. Many factors were reported that related to technique, patient, and dentist, as well as their likelihood of influencing patient satisfaction. The factors presenting reasonable evidence of influencing patient satisfaction are the kind of therapy chosen (implant-retained overdentures rated more favorably than conventional dentures); patient personality and psychological factors; patient oral conditions; patient perception of the dentist and dental care; and patient-dentist communication issues. Several other factors that may influence patient satisfaction were not addressed in the recent literature or presented contradicting results, highlighting the need for more research in this topic.